Iota-Carrageenan Prevents the Replication of SARS-CoV-2 in a Human Respiratory Epithelium Cell Line in vitro - Varese, Augusto; Paletta, Ana; Ceballos, Ana; Palacios, Carlos Adolfo; Figueroa, Juan Manuel; Dugour, Andrea Vanesa (Frontiers in Virology, 2021)
Iota-carrageenan is a sulfated polysaccharide extracted from red seaweeds, which, formulated into a nasal spray, has already been proven safe and effective in viral upper respiratory infections. In Calu-3, a human respiratory epithelium cell line, we explored the activity of a formula of iota-carrageenan and sodium chloride against SARS-CoV-2. In this study, the assayed formula, already approved as a nasal spray for human use, effectively inhibited SARS-CoV-2 infection, providing a more substantial reference for clinical studies or developments.